2015
DOI: 10.1182/blood.v126.23.930.930
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Studies of Cellular Immunotherapy Using Central Memory Derived-CD19-Specific T Cells Following Autologous Stem Cell Transplantation for Patients with High-Risk Intermediate Grade B-Lineage Non-Hodgkin Lymphoma

Abstract: Introduction Efforts to improve the survival of non-Hodgkin lymphoma (NHL) patients with recurrent disease have focused primarily on the use of consolidative myeloablative autologous hematopoietic stem cell transplantation (HSCT). However, the major limitation of HSCT for NHL is the high incidence of relapse, even at maximally tolerated preparative regimen intensities. In a series of phase I studies designed to improve HSCT longterm remission rates, we have assessed the safety and feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These data are consistent with pre-clinical data on a combination of CD4 + and CD8 + subsets in mouse experiments [ 18 ], and CD4 + T cells’ role in supporting and inducing CD8 + T cell memory functions [ 19 ]. Another clinical study on patients with high-risk intermediate grade B-lineage non-Hodgkin lymphoma treated either with first generation CD19-CAR-T using isolated CD8 + T CM subset or with second generation CD19-CAR-T using both CD8 + and CD4 + T CM subsets demonstrated the feasibility and safety of both approaches [ 35 ], although the group of CAR-T with CD4 + and CD8 + T CM and second generation CAR-T cells demonstrated better persistence. Future clinical trials using CAR-T isolated from different T cell subsets will be important for understanding the detailed mechanisms of T cell functions in CAR-T immunotherapy.…”
Section: Role Of Different T Cell Subsets Treg Cells Immune Checmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with pre-clinical data on a combination of CD4 + and CD8 + subsets in mouse experiments [ 18 ], and CD4 + T cells’ role in supporting and inducing CD8 + T cell memory functions [ 19 ]. Another clinical study on patients with high-risk intermediate grade B-lineage non-Hodgkin lymphoma treated either with first generation CD19-CAR-T using isolated CD8 + T CM subset or with second generation CD19-CAR-T using both CD8 + and CD4 + T CM subsets demonstrated the feasibility and safety of both approaches [ 35 ], although the group of CAR-T with CD4 + and CD8 + T CM and second generation CAR-T cells demonstrated better persistence. Future clinical trials using CAR-T isolated from different T cell subsets will be important for understanding the detailed mechanisms of T cell functions in CAR-T immunotherapy.…”
Section: Role Of Different T Cell Subsets Treg Cells Immune Checmentioning
confidence: 99%
“…Thus, more efficient expansion of transferred T cells rather than preexisting T cells enhances CAR-T immunotherapy. Recent clinical trials demonstrated the efficacy of lymphodepletion approaches in improving CAR-T immunotherapy [ 34 , 35 ].…”
Section: Role Of Different T Cell Subsets Treg Cells Immune Checmentioning
confidence: 99%